Correction: Social preferences in the public goods game-An Agent-Based simulation with EconSim. - Christoph Bühren; Jan Haarde; Christian Hirschmann; Janis Kesten-Kühne (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0282112.].